ANTHROPOSOPHY AS EDUCATIONAL PHILOSOPHY (Annual of the Faculty of Philosophy in Skopje, 2009)
Anthroposophy reflects the philosophical bases upon which Rudolph Steiner, among other things, established the Waldorf pedagogy. Anthroposophy represents a vital view of the world which can be applied in several fields of the modern, everyday life, such as: anthroposophie medicine, Waldorf pedagogy eurythmy-as a new art of movements, and it also initiates new impulses in architecture and art.The philosophical and theoretical anthroposophie forms represent the foundation of the numerous teaching methods that are being applied in Waldorf kindergartens and schools, and are reflected in the views of many Waldorf educators and teachers, as well as in the general structuring and orientation of the Waldorf education in the course of the different stages of developmentHence, anthroposophy represents the starting point of the Waldorf pedagogy which has been raised to the level of educational philosophy with its own unique characteristics.
Keywords: ANTHROPOSOPHY; EDUCATIONAL PHILOSOPHY; WALDORF EDUCATION